Estrategias de cobranza para el mejoramiento de la liquidez de Grafitext CIA.LTDA. - Mediavilla Vaca, Ana Inés (2015)
Grafitext Ltd. Co. is a growing company with high levels of investments, a very complex competitive sector, where the market has established a flexibility system regarding the credit policies by imposing long periods of informality in the payments from the customers. These, among other factors have caused problems regarding the financial liquidity of the company which is the main objective of this academic piece in order to develop improvements concerning the financial liquidity of the company, in terms of receivable accounts. In the following part, you will find a general detail of the aspects to be analyzed. In chapter I the theorical framework, general and specific objectives, the company is turning point and the scope of this document will be defined. In chapter II the importance of correct cash management within a company will be theoretically established. This is the content base of the chapter. In chapter III a macroeconomic analysis of the actual situation of the Ecuadorian graphic industry is described, and in chapter IV you will find an analysis of Grafitext Ltd. Co. during year 2013. In chapter V the company is redesign of the credit, collection and payment departments program will be established, as well as all the tools and strategies involved in the process. In chapter VI a financial evaluation will be made, all conclusions and results of the project developed in 2014 will be presented in this chapter as well. The main conclusion of this academic work is that the practical implementation of financial collection strategies established during this project, have improved the liquidity indexes of the company.